Attentional Processing and Interpretative Bias in Functional Neurological Disorder. Issue 6 (July 2020) - Keynejad, Roxanne C.; Fenby, Edward; Pick, Susannah; Moss-Morris, Rona; Hirsch, Colette; Chalder, Trudie; Hughes, Alicia M.; Nicholson, Timothy R.
ABSTRACT: Objective: Altered attentional processing (automatically attending to negative or illness-relevant information) and interpretative biases (interpreting ambiguous information as negative or illness relevant) may be mechanistically involved in functional neurological disorder (FND). Common mechanisms between FND and chronic fatigue syndrome (CFS) have been proposed but not compared experimentally. Methods: We compared the cognitive task performance of FND, CFS, and healthy control (HC) groups. The tasks assessed attentional bias toward illness-relevant stimuli (visual probe task), attentional control (attention network task), and somatic interpretations (interpretative bias task), alongside self-reported depression, anxiety, fatigue, and general health. Results: Thirty-seven participants diagnosed with FND, 52 participants diagnosed with CFS, and 51 HC participants were included. Although participants with CFS showed attentional bias for illness-relevant stimuli relative to HC ( t = −3.13, p = .002, d = 0.624), individuals with FND did not ( t = −1.59, p = .118, d = 0.379). Both the FND ( t = 3.08, p = .003, d = 0.759) and CFS ( t = 2.74, p = .007, d = 0.548) groups displayed worse attentional control than did the HC group. Similarly, the FND ( t = 3.63, p < .001, d = 0.801) and CFS groups ( t = 4.58, p < .001, d = 0.909) showed more somatic interpretative bias than did the HC group. Conclusions: Similar attentional control deficits and somatic interpretative bias in individuals with FND and CFS support potential shared mechanisms underlying symptoms. Interpretative bias toward somatic and illness-relevant stimuli in functional disorders may prove a therapeutic target. Abstract : Supplemental digital content is available in the text.